Analysis of the Effectiveness of Diorama in Visualizing Science Concepts and Fostering Creative Thinking Skills Among Elementary School Students: A Systematic Literature Review - Lingling Diliyanti; Rohmani Rohmani (Institute of Multidisciplinary Research and Community Service, 2026)
Science teaching in primary schools often faces challenges in explaining abstract material, making it difficult for pupils to fully grasp the concepts. One medium that can aid in visualizing these concepts is the diorama, a three-dimensional display that presents objects or events in miniature, resembling real-life conditions. This study aims to explore the use of dioramas to visualize science concepts and their relationship to the development of creative thinking skills in primary school pupils. The method used in this study is a Systematic Literature Review (SLR) conducted in accordance with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. The research stages include identification, screening, eligibility assessment, and article inclusion. Data were obtained through a search of scientific articles in the Google Scholar database covering the publication period 2021–2025 using relevant keywords. The articles found were then selected based on inclusion and exclusion criteria, resulting in several articles suitable for further analysis. Subsequently, the articles were analyzed descriptively to identify patterns of findings regarding the use of dioramas in science learning in primary schools. The study's findings indicate that dioramas play a positive role in helping pupils understand abstract science concepts more concretely. Furthermore, dioramas enhance pupil engagement through activities such as observation, discussion, and the expression of ideas. The diorama supports the development of flexible thinking, original ideas, and the ability to elaborate on them. Several studies also indicate that integrating dioramas with project-based learning yields more optimal results in enhancing pupils’ creativity. The implications of this research suggest that dioramas can serve as an effective alternative teaching method to improve the quality of science education in primary schools, both in terms of conceptual understanding and the development of pupils’ creative thinking skills. Keywords: Diorama media, Elementary school science, Creative thinking skills.